Can Reinvigorated Faculty Recommit to Elevating Health Science Learning Experiences? Exploratory Perspectives from G20 and GCC Countries - Mustafa M. Bodrick; Lobna A. Aljuffali; Mohammed Y. Alrasi; Abdullah A. Alhawas; Aws A. Obaid (British Journal of Teacher Education and Pedagogy, 2026)
Synthesizing literature across Group of Twenty (G20) and Gulf Cooperation Council (GCC) countries, this study examines whether reinvigorated faculty can recommit successfully to elevating undergraduate learning experiences for Gen Z students in health science programs. Driven by rapid global innovation, this transformation centers on competency-based learning, which overhauls traditional teaching models. This review assesses the transition to activity-based, experiential, and technology-driven approaches, specifically considering artificial intelligence, machine learning, virtual reality, and gamification in the optimization of educational experiences and outcomes. Furthermore, it addresses essential structural and psychological barriers, examining targeted training programs to mitigate tech anxiety alongside faculty networking and peer review to facilitate transitions that are crucial to reinvigoration. Finally, the study highlights the leadership prerequisites of clear governance, accountability structures, and mental health referral systems to support faculty in managing contemporary student dynamics, including Gen Z attributes and students with Attention Deficit Hyperactivity Disorder (ADHD). Ultimately, this landscape of international insights positions systemic faculty development as a critical strategic priority for advancing health science education and enriching the undergraduate learning journey and experiences.